Testicular microlithiasis and dyspermia: Is there any correlation? - Francesco Catanzariti; Ubaldo Cantoro; Vito Lacetera; Giovanni Muzzonigro; Massimo Polito (Archivio Italiano di Urologia e Andrologia, 2014)
Background: Testicular microlithiasis (MT) is an uncommon sonographic finding (prevalence in the literature: 0.7 to 6%). Several studies have highlighted its possible correlation with an increased risk of testicular cancer, but few studies have investigated its possible link with dyspermia. Objectives: The aim of our study was to investigate in our series the number of patients with microlithiasis, diagnosed by ultrasound, and compare the quality of their sperm with that of patients in a control group with normal testicular ultrasound exam. Materials and methods: We performed 277 consecutive testicular ultrasound examinations from January 2012 to July 2012. Among all these, we selected 86 patients that showed no pathological elements at echography and 11 patients affected by MT, to one or both testicles. Each patient was also submitted to a short-term semen analysis using the WHO2010 parameters for sperm evaluation. Results: Among 11 patients with MT, 7 (63.63%) were dyspermic and 4 (36.36%) were normospermic. Among the 86 patients with normal testicular ultrasound 51 (59.3%) were dyspermic, 4 (4.65%) were azoospermic, while the remaining 31 (36.05%) were normospermic. Comparing the results of the two groups we obtained an odds ratio of 0.99 (95% CI: 0.27 to 3.64, p: 0.98). Conclusions: This study, although preliminary, with a low number of partecipants, shows that sperm quality is not affected by the presence of testicular microlithiasis, because the results of spermiograms are almost comparable between the two groups.